Practice Teachers Possible Solutions to Students Problems of Speaking during PPL in Junior High Schools - Isworo, Chezia Eufresia (LLT Journal: A Journal on Language and Language Teaching, 2016)
Program Pengalaman Lapangan (PPL) or School-based Practicum is one of the compulsory courses that must be taken by all English Language Education Study Program (ELESP) Sanata Dharma University students. PPL requires the students, who are called practice teachers, to do teachers job at school. As English practiceteachers, there is a possibility that they might face a lot of problems related to thecondition and situation in the school, either from the students side, teachers side,or other factors. This research focuses on junior high school students problems of speaking and the possible solutions to the problems based on the ELESP students experiences as English practice teachers. From the findings, it is expected that future practice teachers and English teachers can anticipate similar problems and apply the possible solutions when they work at schools.